Economic cycles and social movements : past, present and future - Mielants, Eric; Bardos, Katsiaryna Salavei (New York, NY : Routledge, 2021)
Economic Cycles and Social Movements: Past, Present and Future offers diverse perspectives on the complex interrelationship between social challenges and economic crises in the Modern World System. Written with a balance of quantitative, qualitative and theoretical contributions and insights, this volume provides a great opportunity to reflect upon the ongoing conceptual and empirical challenges when confronting the complex interrelations of various economic cycles and social movements. By engaging wide-ranging ideas and theoretical points of view from different disciplines, different countries and different perspectives, this study breaks new ground and offers novel insights into the way the capitalist world economy functions as well as the way social and political movements react to these constraints. Different chapters in this volume bring about novel interdisciplinary approaches to study business cycles, economic changes and social as well as political movements, offer new interpretations and, while examining the complexity of socioeconomic cycles in the long run, present epistemological challenges and a wide variety of empirical data that will increase our understanding of these complex interactions.
OCLC-licensed vendor bibliographic record.
Keywords: Business cycles; Social movements; Business and politics; SOCIAL SCIENCE / Emigration & Immigration; SOCIAL SCIENCE / Social Classes; SOCIAL SCIENCE / Third World Development